Health care ethics critical issues for the 21st century - Morrison, Eileen E.; Furlong, Elizabeth (Jones & Bartlett Learning, 2019)
The fully revised and updated Fourth Edition addresses current changes in health care, including three new chapters covering ethical issues related to Health Information Management, Patient Safety, and Epidemics. All other chapters have been updated to reflect the most recent developments in medical technology and new challenges faced by health care professionals in the era of the ACA.